Perancangan User Interface pada Website The Royale Krakatau Hotel Cilegon menggunakan Metode Goal Directed Design - Tresnamayu Rahma Dika; Tri Sagirani; Puspita Kartikasari (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2020)
The Royale Krakatau Hotel Cilegon is a 4 star hotel located on Jl. KH. Yasin Beji No.4 Cilegon, Banten. The Royale Krakatau Cilegon Hotel has a website that can be accessed with the link www.royalekrakatau.com. There are several obstacles from the website, namely the design of the user interface that is less attractive, complicated website flow, the main menu is difficult to find, the text is not legible clearly, the image size is too large, and the placement of content is not right. From these problems, the evaluation results using the Quality in Use Integrated Measurement (QUIM) method show problems with a high priority level of improvement found in the variables of effectiveness, satisfaction, and universality. Therefore a redesign was carried out using the Goal Directed Design (GDD) method. The steps in the GDD method are Research, Modeling, Requirement Definition, Framework Definition, and Refinement. Redesign has been compiled and tested. The final evaluation results on the website redesign carried out on respondents using the QUIM method, the average value obtained is 3.7 from the Likert scale with a rating scale instrument having a rating of 1 to 4, value 3 means good enough and there are no significant problems.